The Effect of Ferula Assafoetida Hanging on the Morphometric Changes of the Reproductive Organs of the Rocks (Texas Journal of Agriculture and Biological Sciences, 2022)
In this article, the morphometric changes of the reproductive organs in the postnatal ontogeny of Karakol cows under the influence of Ferula assafoetida fertility are presented